Light Scattering Reviews 7 Radiative Transfer and Optical Properties of Atmosphere and Underlying Surface - Kokhanovsky, Alexander A. (Springer Praxis Books, 2013)
Light Scattering Reviews (vol.7) is aimed at the description of modern advances in radiative transfer and light scattering. The following topics will be considered: the spherical harmonics method, light scattering by densely packed systems of particles, Markovian approach for radiative transfer in cloudy atmospheres, coherent and incoherent backscattering by turbid media and surfaces, advances in radiative transfer methods as used for luminiscence tomography, optical properties of oceanic water, spectral reflectance of forest stand and snow.This volume will be a valuable addition to already published volumes 1-6 of Light Scattering Reviews.